A Preliminary Anthropometric Study of Footprint Dimensions as a Model for Height Estimation - Addai, Raymond; Abaido, Chrissie Stansie; Appiah, Atta Kusi (Academia Anatomica International, 2017)
Background: Height is an important pillar used in biological profiling. Several human body parts including footprints have been employed in developed countries for forensic and biometric purposes. Little information on footprint dimensions and height is available in Ghana. Hence, this study was conducted to determine the relationship between height and footprint dimensions in a Ghanaian population. Methods: Bilateral footprints were obtained from 93 undergraduate students (53 males and 40 females) aged between 18 and 43 years from the Kwame Nkrumah University of Science and Technology, School of Medical Sciences from January 2016 to April 2016using an ink pad and white papers. Seven dimensions: five length dimensions from the most anterior part of each toe to the mid-rear heel point, pterion (designated PT1-PT5), breadth at ball (BAB) and breadth at heel (BAH) were obtained from each footprint. Results: Males were found to be taller and with longer footprint dimensions than females. Left footprint dimensions were longer than right footprint dimensions. Bilateral asymmetry were observed in PT1 and BAH in both sexes, PT2 in females only and BAB in males only. Statistically significant positive correlations were observed between height and the left or right footprint lengths from the pterion to all the toes. In males, combinations of PT1 and PT4 accounted for 57.9% variation in height estimation for the right foot and 55% of the variation for the left foot. In the female participants, PT1 of the right foot accounted for 54.9% variation in height estimation whereas PT3 of the left foot accounted for 56.5% of height prediction. Conclusion: PT1, PT2 and PT4 were stronger predictors of height in males whereas PT1 and PT3were better estimators of height in females. Footprint dimensions are useful in height estimation.